Peningkatan Kemampuan Sains Anak Melalui Metode Eksperimen Balon Ilmiah Pada Anak Di Taman Kanak-kanak Islam Bunayya - Arbayah; Rosevina Saleh, Quinta; Sjamsir, Hasbi (Manajemen Pendidikan Program Doktor, 2022)
The background of research at Bunayya Islamic Kindergarten is that there are still many children in the B1 group whose science skills are still lacking. Children are less motivated to discover new facts, explore and tackle discovered problems. Therefore, through experimental methods, scientific balloons can improve children's science skills in cognitive development. The formulation of the problem in this study is